Phenomenological study of seismic anisotropy in Shales - Pervukhina, Marina; Golodoniuc, P.; Dewhurst, D. (European Association of Geoscientists and Engineers, EAGE, 2013)
Copyright © (2012) by the European Association of Geoscientists & Engineers All rights reserved. Elastic anisotropy is important for a number of geophysical applications, including seismic interpretation, fluid identification and 4D seismic monitoring. Due to their strongly anisotropic properties, the presence of shales in the subsurface may cause significant errors in depth obtained from surface seismic data, in normal and dip moveout correction, migration and amplitude versus offset analysis. Here we analyze Thomsen's anisotropy parameters and anellipticities of 37 shales with different mineralogical compositions, maximum overburden stress experienced, silt and clay fractions, porosities and other petrophysical parameters. The shales extracted from depths below 4000 m exhibit the largest values of Pand S-wave anisotropies, while negative delta values are mostly observed for shales extracted from shallow depths. The observed diversity of Thomsen's anisotropy parameters and anellipticities can be explained with (1) intrinsic anisotropy of wet clay packs, (2) governed by compaction anisotropic distribution of discontinuities and (3) effects of aligned silt inclusions on shale elastic properties.